Discretionary role of the provisions of the Court of Cessation - العبودي, عباس زبون (Journal of Legal Sciences, 2019)
Discretionary role of the provisions of the Federal Court of Cassation occupies a distinct role in the drafting of the legal base, thanks to vocational and higher professional level, which is practiced by this court in the adaptation of the civil law in light of the changing conditions of the community with the survival of inertia that characterizes the legal basis, so that the legislator important for precision and perfection in his work in drafting this rule, it cannot take in everything and put the necessary solutions to all the new issues that appear in the society. Therefore, the courts in this case is keen to reconcile the provisions of fixed base and the changing conditions of society , in order to reach the intent of the legislature and give new meaning fixed base , be more suited to the conditions of the society in which they are applied.